Differential protein repertoires related to sperm function identified in extracellular vesicles (EVs) in seminal plasma of distinct fertility buffalo (Bubalus bubalis) bulls - Badrhan, Shiva; Karanwal, Seema; Pal, Ankit; Chera, Jatinder Singh; Chauhan, Vitika; Patel, Aditya; Bhakat, Mukesh; Datta, Tirtha K.; Kumar, Rakesh (Frontiers in Cell and Developmental Biology, 2024)
Buffalo bulls are backbone of Indian dairy industry, and the quality of semen donating bulls determine the overall production efficiency of dairy farms. Seminal plasma (SP) harbor millions of lipid bilayer nanovesicles known as extracellular vesicles (EVs). These EVs carry a heterogenous cargo of essential biomolecules including fertility-associated proteins which contribute to fertilizing potential of spermatozoa. In this study, we explored size, concentration, and complete proteome profiles of SP EVs from two distinct fertility groups to uncover proteins influencing bull fertility. Through Dynamic Light Scattering (DLS) it was found that purified EVs were present in 7 to 14 size exclusion chromatographic (SEC) fractions with sizes ranging from 146.5 to 258.7 nm in high fertile (HF) and low fertile (LF) bulls. Nanoparticle Tracking Analysis (NTA) confirmed the size of seminal EVs up to 200 nm, and concentrations varying from 2.84 to 6.82 × 10 11 and 3.57 to 7.74 × 10 11 particles per ml in HF and LF bulls, respectively. No significant difference was observed in size and concentration of seminal EVs between two groups. We identified a total of 1862 and 1807 proteins in seminal EVs of HF and LF bulls, respectively using high throughput LC-MS/MS approach. Out of these total proteins, 1754 proteins were common in both groups and about 87 proteins were highly abundant in HF group while 1292 were less abundant as compared to LF bulls. Gene ontology (GO) analysis, revealed that highly abundant proteins in HF group were mainly part of the nucleus and involved in nucleosome assembly along with DNA binding. Additionally, highly abundant proteins in EVs of HF group were found to be involved in spermatogenesis, motility, acrosome reaction, capacitation, gamete fusion, and cryotolerance. Two highly abundant proteins, protein disulfide-isomerase A4 and gelsolin, are associated with sperm-oocyte fusion and acrosome reaction, respectively, and their immunolocalization on spermatozoa may indicate that these proteins are transferred through EVs. Our evidences support that proteins in EVs and subsequently their presence on sperm, are strongly associated with sperm functions. Altogether, our investigation indicates that SPEVs possess crucial protein repertoires that are essential for enhancing sperm fertilizing capacity.